Genomic classification of the RAS network identifies a personalized treatment strategy for lung cancer. Issue 7 (20th May 2014) - El-Chaar, Nader N.; Piccolo, Stephen R.; Boucher, Kenneth M.; Cohen, Adam L.; Chang, Jeffrey T.; Moos, Philip J.; Bild, Andrea H.
Abstract : Better approaches are needed to evaluate a single patient's drug response at the genomic level. Targeted therapy for signaling pathways in cancer has met limited success in part due to the exceedingly interwoven nature of the pathways. In particular, the highly complex RAS network has been challenging to target. Effectively targeting the pathway requires development of techniques that measure global network activity to account for pathway complexity. For this purpose, we used a gene‐expression‐based biomarker for RAS network activity in non‐small cell lung cancer (NSCLC) cells, and screened for drugs whose efficacy was significantly highly correlated to RAS network activity. Results identified EGFR and MEK co‐inhibition as the most effective treatment for RAS‐active NSCLC amongst a panel of over 360 compounds and fractions. RAS activity was identified in both RAS‐mutant and wild‐type lines, indicating broad characterization of RAS signaling inclusive of multiple mechanisms of RAS activity, and not solely based on mutation status. Mechanistic studies demonstrated that co‐inhibition of EGFR and MEK induced apoptosis and blocked both EGFR‐RAS‐RAF‐MEK‐ERK and EGFR‐PI3K‐AKT‐RPS6 nodes simultaneously in RAS‐active, but not RAS‐inactive NSCLC. These results provide a comprehensive strategy to personalize treatment of NSCLC based on RAS network dysregulation and provide proof‐of‐concept of a genomic approach to classify and target complex signaling networks. Highlights: RAS gene‐expression profiling evaluates patient drug response at the pathway level. Co‐inhibition of EGFR and MEK is an effective treatment against RAS‐active NSCLC. Genomic biomarker for RAS‐pathway activity, not KRAS mutation, predicts the response. EGFR and MEK inhibition induces apoptosis and blocks ERK and RPS6 in RAS‐active NSCLC. Personalization of EGFR + MEK treatment to RAS‐active NSCLC necessary for effectiveness.